2021
DOI: 10.1371/journal.pone.0253945
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical predictors of experimental muscle pain intensity following fatiguing calf exercise

Abstract: Musculoskeletal pain affects approximately 20% of the population worldwide and represents one of the leading causes of global disability. As yet, precise mechanisms underlying the development of musculoskeletal pain and transition to chronicity remain unclear, though individual factors such as sleep quality, physical activity, affective state, pain catastrophizing and psychophysical pain sensitivity have all been suggested to be involved. This study aimed to investigate whether factors at baseline could predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…The Osteoarthritis Research Society International (OARSI) recommends duloxetine (a strong serotonin and noradrenaline re‐uptake inhibitor anti‐depressant) as a treatment option for patients with OA and/or widespread pain (Bannuru et al, 2019). Pain catastrophizing has often been found as a predictor of future pain (Kristensen et al, 2021; Larsen, Laursen, Edwards, et al, 2021; Petersen et al, 2020) and higher levels of pain catastrophizing, anxiety and depression are found in OA patients with poor quality of sleep when compared with patients with good quality of sleep (Larsen, Laursen, Simonsen, et al, 2021). A recent study on OA demonstrated that the combination of pre‐treatment QST, psychological factors and clinical pain could predict the analgesic effect of 14 weeks of duloxetine (Petersen et al, 2022), which underlines the importance of incorporating psychological factors in pain profiling of patients with OA.…”
Section: Discussionmentioning
confidence: 99%
“…The Osteoarthritis Research Society International (OARSI) recommends duloxetine (a strong serotonin and noradrenaline re‐uptake inhibitor anti‐depressant) as a treatment option for patients with OA and/or widespread pain (Bannuru et al, 2019). Pain catastrophizing has often been found as a predictor of future pain (Kristensen et al, 2021; Larsen, Laursen, Edwards, et al, 2021; Petersen et al, 2020) and higher levels of pain catastrophizing, anxiety and depression are found in OA patients with poor quality of sleep when compared with patients with good quality of sleep (Larsen, Laursen, Simonsen, et al, 2021). A recent study on OA demonstrated that the combination of pre‐treatment QST, psychological factors and clinical pain could predict the analgesic effect of 14 weeks of duloxetine (Petersen et al, 2022), which underlines the importance of incorporating psychological factors in pain profiling of patients with OA.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise-induced LBP inducing moderate pain for several days did not facilitate the TSP when assessed on the legs, but interestingly, the baseline degree of TSP was associated with the pain intensity of the experimentally induced LBP 158 and similarly when provoking long-term pain in the calf muscle. 127 In summary, summation of pain often assessed distant to the pain locus is generally facilitated in musculoskeletal pain conditions compared with asymptomatic controls or compared with pain-free periods in the same individuals, suggesting that this is a state of the pain system, although with an important prognostic value for pain persistence and treatment outcome. However, the TSP may also hold some trait characteristics of the pain system because it also predicts the degree of experimental long-term pain conditions in otherwise asymptomatic controls.…”
Section: Musculoskeletal Pain Summation As a Predictor For Pain Progr...mentioning
confidence: 94%
“…Exercise-induced LBP inducing moderate pain for several days did not facilitate the TSP when assessed on the legs, but interestingly, the baseline degree of TSP was associated with the pain intensity of the experimentally induced LBP 158 and similarly when provoking long-term pain in the calf muscle. 127…”
Section: Introductionmentioning
confidence: 99%
“…At this point, the patient was instructed to press a stop button. The pressure pain detection threshold (cPDT) was defined as the pressure at which the VAS score exceeded 1 cm as in previous studies (Kristensen et al, 2021; Larsen, Laursen, Edwards, et al, 2021; Petersen, Simonsen, et al, 2019). The pain tolerance threshold (cPTT) was defined when the patient pressed the stop button.…”
Section: Assessmentsmentioning
confidence: 99%